Effects of Deglobalization on Food and Energy Insecurity in the GMS Countries - Nonthapot, Sakkarin; Watchalaanun, Tanawat (International Journal of Energy Economics and Policy, 2023)
Amidst the trend of globalization, which has been disrupted by various global situations such as trade wars, the pandemic, and the effects of war, concerns about deglobalization have arisen, particularly among countries vulnerable to food and energy insecurity. The aim of this study was to analyze the effects of deglobalization on the food and energy insecurity of Greater Mekong Subregion (GMS) countries. Food insecurity was determined by the percentage of malnourished people within a country, while energy insecurity was determined by the percentage of dependence on oil energy imports. Such influences were found to be transmitted through price factors and each country’s level of participation in globalization. A simultaneous equation was analyzed to determine the correlations. The findings of the study were as follows: 1) Deglobalization will increase food insecurity in Cambodia, Laos, Myanmar, and Thailand as they become less involved in globalization, but will decrease it as the effects of deglobalization are transmitted to the price factors for China, Laos, Myanmar, and Thailand. 2) When the influence of deglobalization is transmitted through the price factors, it could increase China’s energy insecurity but reduce energy insecurity for Vietnam. Additionally, the impact of deglobalization has increased the energy insecurity of Laos, Myanmar, and Vietnam, as their involvement in globalization is linked to such influences.